Asymptomatic players with a patellar tendon abnormality do not adapt their landing mechanics when fatigued. Issue 8 (18th April 2017) - Edwards, Suzi; Steele, Julie R.; McGhee, Deirdre E.; Purdam, Craig R.; Cook, Jill L.
ABSTRACT: This study aimed to explore how asymptomatic athletes with a patellar tendon abnormality (PTA), who are at high risk of developing patellar tendinopathy, alter their landing technique and net patellar tendon loads generated in response to fatigue. Seven asymptomatic players with a PTA performed five successful vertical stop-jump trials before and after a fatigue protocol. Fatigue protocol involved participants repeatedly performing sets of 30 submaximal jump exercises on a sledge apparatus followed by 30 s rest until the task failure criteria were reached. Three-dimensional ground reaction forces, lower limb kinematics and net peak patellar tendon force were recorded during the stop-jump task. No significant between-fatigue condition differences in net patellar tendon loading, or most secondary outcome variables were observed. Only some fatigue changes were seen during the vertical landing phase. Asymptomatic PTA participants did not modify their landing technique or net patellar tendon loading during a stop-jump task in response to fatigue. The lack of between-fatigue condition differences displayed by the asymptomatic PTA participants during both landing phases suggest that these individuals may not be capable of sufficient movement variability in their landing strategies to adapt to fatigue.